2004
DOI: 10.1016/j.jmb.2004.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium tumefaciens VirB6 Domains Direct the Ordered Export of a DNA Substrate Through a Type IV Secretion System

Abstract: The Agrobacterium tumefaciens VirB/D4 type IV secretion system (T4SS) translocates DNA and protein substrates across the bacterial cell envelope. Six presumptive channel subunits of this T4SS (VirD4, VirB11, VirB6, VirB8, VirB2, and VirB9) form close contacts with the VirD2-Tstrand transfer intermediate during export, as shown recently by a novel transfer DNA immunoprecipitation (TrIP) assay. Here, we characterize the contribution of the hydrophobic channel component VirB6 to substrate translocation. Results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
131
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(138 citation statements)
references
References 66 publications
4
131
1
2
Order By: Relevance
“…The A. tumefaciens T4SS protein VirB6 also localizes to the poles; however, like TrhC from the R27 plasmid, this localization is dependent on the presence of a subset of conjugative proteins, VirB7-VirB11 (Judd et al, 2005). However, this dependence of VirB6 positioning on Ti-plasmid-encoded VirB proteins was not demonstrated in a recent study, suggesting that additional work is required to resolve the architecture and temporal assembly of the Vir T4SS (Jakubowski et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The A. tumefaciens T4SS protein VirB6 also localizes to the poles; however, like TrhC from the R27 plasmid, this localization is dependent on the presence of a subset of conjugative proteins, VirB7-VirB11 (Judd et al, 2005). However, this dependence of VirB6 positioning on Ti-plasmid-encoded VirB proteins was not demonstrated in a recent study, suggesting that additional work is required to resolve the architecture and temporal assembly of the Vir T4SS (Jakubowski et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
“…VirD4 was found to associate with the poles of A. tumefaciens, and this polar localization was determined to occur in the absence of other essential conjugation proteins (Kumar & Das, 2002). Subsequent localization experiments with A. tumefaciens revealed that a T4SS protein, VirB6, co-localized with VirD4 at the poles of the cell (Jakubowski et al, 2004;Judd et al, 2005). In contrast, a GFP fusion to the T4SS protein TrhC from R27 revealed that this VirB4 homologue was found at random positions around the periphery of the cell (Gilmour et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…VirB6 is a polytopic inner-membrane protein that forms part of the lumen of the Mpf channel structure, as detected by TrIP analysis in A. tumefaciens (Cascales and Christie, 2004b;Jakubowski et al, 2004). Together with VirB8, VirB6 is required for delivery of the T-DNA substrate to the outermembrane-associated components VirB2 and VirB9 (Cascales and Christie, 2004b).…”
Section: Virb6: a Modulator Of The Secretion Channel?mentioning
confidence: 99%
“…Conversely, the presence of VirB6 is required for stable expression of VirB3 and VirB5 and for formation of VirB7 homodimers and VirB7-VirB9 heterodimers (Hapfelmeier et al, 2000;Jakubowski et al, 2003;Krall et al, 2002). The domains of VirB6 mediating polar localization, interaction with the T-DNA substrate, substrate transfer to VirB8 or substrate transfer to VirB2 and VirB9 have been delimited (Jakubowski et al, 2004;Judd et al, 2005). These data on A. tumefaciens VirB6 clearly demonstrate the importance of VirB6 as a central channel component engaged in a series of substrate-and Mpf-component interactions.…”
Section: Virb6: a Modulator Of The Secretion Channel?mentioning
confidence: 99%
“…Three NTPases (VirB4, -B11, and -D4) comprise the cytoplasmic component of the system and are closely associated with the inner membrane (2). VirB6 has multiple transmembrane helices and forms an inner membrane complex with VirB8 and VirB10 (11). VirB8 and VirB10, however, are largely periplasmic, each possessing a short cytoplasmic N-terminal tail, a single transmembrane helix, and a large conserved periplasmic C-terminal domain separated from the helix by a nonconserved linker sequence.…”
mentioning
confidence: 99%